Limited Imprisonment: A Concept of Combining Imprisonment and Probation - Zuliah, Emi; Zahrani, Fadia Zahrani (Universitas Islam Negeri Sumatera Utara, 2022)
This research aims to explore and analyze the idea of limited imprisonment as a combination of imprisonment and supervision. The main focus of the research is to understand the purpose, methodology, and findings related to this innovative concept in the context of criminal justice. The main objective of the research is to identify the potential benefits and challenges of implementing limited imprisonment in the criminal justice system. The research methodology involved a combinative approach of legal literature analysis, case studies, and interviews with legal experts and criminal law practitioners. This examination of ideas was conducted by analyzing the legal aspects, social impacts, and practical feasibility of sanctioning violations of the law. The research findings suggest that limited imprisonment has the potential to provide a more humane and effective alternative in dealing with minor or non-violent offenses. Advantages include flexibility in sentencing, reduced prison burden, and providing greater rehabilitation opportunities for offenders. However, challenges such as the risk of abuse, legal uncertainty, and the need for clear regulation were also identified. This research contributes to the development of thinking in the field of criminal law, proposing an in-depth consideration of the implementation of limited imprisonment. Implications include the need for further study and further discussion in order to develop a framework that can answer legal, ethical, and policy questions related to the implementation of this idea in the criminal justice system.